2015
DOI: 10.5194/aab-58-433-2015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different cryoprotectants on the cryopreservation of cattle testicular tissue

Abstract: Abstract. Cryopreservation of testicular tissue is a new option in fertility preservation for prepubertal male animals. The purpose of this study was to explore the effects of different cryoprotectant agents (CPAs) at various concentrations on testes after the cryopreservation of calf testicular tissue. These experiments selected dimethyl sulfoxide (DMSO), glycerol, propylene glycol (PrOH), and sucrose as CPAs in varying doses (2.5, 5, 7.5, 10, 12.5, 15, 17.5, and 20 %; v/v) in 8-month-old calf testicular tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…MDA as a serum metabolic indicator can indirectly reflect the severity of myocardial cell injury . SOD is the main antioxidant enzyme in the body, which protects cells from free radical damage by scavenging oxygen free radicals . Therefore, it can be seen that in IRI mice, cardiomyocytes are damaged by oxygen free radicals, and OS is also enhanced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MDA as a serum metabolic indicator can indirectly reflect the severity of myocardial cell injury . SOD is the main antioxidant enzyme in the body, which protects cells from free radical damage by scavenging oxygen free radicals . Therefore, it can be seen that in IRI mice, cardiomyocytes are damaged by oxygen free radicals, and OS is also enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…28 SOD is the main antioxidant enzyme in the body, which protects cells from free radical damage by scavenging oxygen free radicals. 29 Therefore, it can be seen that in IRI mice, cardiomyocytes are damaged by oxygen free radicals, and OS is also enhanced. Our results also demonstrated that the overexpressed miR-590-3p and silenced RIPK1 showed increased Bcl-2 expression, and decreased expression of RIPK1, NF-κB, TLR4, caspase-3, FasL, p53, and cmyc.…”
Section: Downregulated Ripk1 Prolonged Cell Cycle Distribution and In...mentioning
confidence: 99%
“…Cell viability depends on the thawing method, duration of cold storage, and reagents used (33). Relatively short storage periods (34) and optimal concentration of DMSO (10%) are crucial factors contributing to high cell viability in cryopreserved condition (32,(34)(35)(36). Other conditions not mentioned here may have an impact on the high cell viability in this study.…”
Section: Discussionmentioning
confidence: 82%
“…Cell viability depends on the thawing method, duration of cold storage, and reagents used [36]. Relatively short storage periods [37] and optimal concentration of DMSO (10%) are crucial factors contributing to high cell viability in cryopreserved conditions [35,[37][38][39]. Other conditions not mentioned here may have an impact on the high cell viability in this study.…”
Section: Discussionmentioning
confidence: 82%